2006
DOI: 10.1071/ea04207
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield responses of apricot (cv. Moorpark) to soil-applied nitrogen

Abstract: The effect of soil-applied nitrogen on the growth and yield of 12-year-old apricot Prunus armeniaca cultivar Moorpark trees growing on an orthic Tenosol in the Riverland region of South Australia was studied over 3 years. The experiment was set up in a randomised complete block design with 6 annual rates of nitrogen (0, 250, 500, 750, 1000 and 1250 g/tree.year) applied in the form of ammonium nitrate. Application was split into 30% at budburst, 30% 6 weeks after budburst and 40% after harvest. Growth in trunk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The results are in line with Rettke et al (2006) who reported that orchard with fertilizer application having macronutrients of Nitrogen (N), Phosphorus (P) and Potassium (K) significantly increased the fruit yield and fruit size as compared to control orchard.…”
Section: Effects Of Fertilizers On Productionsupporting
confidence: 89%
“…The results are in line with Rettke et al (2006) who reported that orchard with fertilizer application having macronutrients of Nitrogen (N), Phosphorus (P) and Potassium (K) significantly increased the fruit yield and fruit size as compared to control orchard.…”
Section: Effects Of Fertilizers On Productionsupporting
confidence: 89%
“…But how this biomass is distributed among the developing buds (fruits and proleptic axes) is still discussed. The relation between the number and the size of the fruits and the fertilisation of the previous year was more investigated (Neilsen et al 2001;Rettke et al 2006), but the results could partly be attributed to the fact that fertilisation, applied during shoot growth, increased phytomers production, and consequently the number of reproductive buds.…”
Section: Introductionmentioning
confidence: 98%
“…Nitrogen effect on leaf color the second seaon was similar to the first. Rettke et al (2006) used a Minolta chroma meter to show N applications to fieldgrown apricot trees resulted in darker and greener leaves. The Minolta chroma meter was found to provide a reliable indication of turfgrass leaf chlorophyll content and was considered to have the potential to guide N management (Mangiafico and Guillard, 2005).…”
Section: Discussionmentioning
confidence: 99%